The quantum world of ultra-cold atoms and light, Book III, Ultra-cold atoms - Gardiner, Crispin W. 1942- (World Scientific Publishing Europe Ltd., 2017)
"This century has seen the development of technologies for manipulating and controlling matter and light at the level of individual photons and atoms, a realm in which physics is fully quantum-mechanical. The dominant experimental technology is the laser, and the theoretical paradigm is quantum optics. The Quantum World of Ultra-Cold Atoms and Light is a trilogy, which presents the quantum optics way of thinking and its applications to quantum devices. This book — "Ultra-Cold Atoms" — provides a theoretical treatment of ultra-cold Bosons and Fermions and their interactions with electromagnetic fields in a form consistent with the first two books in the trilogy. The central concept is the quantum stochastic paradigm, formulated for cold collision physics. For Bosons, this yields a suite of techniques; versions of the stochastic Gross–Pitaevskii equation, using which a wide range of dynamic and thermal properties are formulated."--Publisher's website
Title from PDF title page (viewed September 8, 2017)
Keywords: Quantum optics; Low temperatures; Light; Bose-Einstein condensation; Bosons; Fermions; Stochastic processes; Electronic books